(untitled) (UNED Research Journal, 2021)
Introduction: The horse (Equus caballus) is an adaptable large herbivore distributed in a wide range of terrestrial biomes that negatively affects ecosystems around the world. Most research on horse–ecosystems interactions have been focused on plants and soils, whereas horse effects on vertebrate species are poorly understanded. Objective: We aimed to synthesize, at a global scale, the effects of free-roaming horses on wild mammals. Methods: We conducted a systematic literature review that included these words; "feral horses + competition ", "feral horses + interactions", "feral horses + impacts", "feral horses + effects", based on the “Web of Science” internet search engine. Results: We located 366 articles in our search, but only 14 peer-reviewed documents described the effects of horses on local wild mammals. Most studies were published in the last decade (64%), and were located in United States (64%). Additional information showed most studies used correlational approaches while experimental approaches were used less. The effect of horses on mammal taxonomic groups varied significantly, suggesting changes on habitat structure mostly affects vertebrate species such as small rodents. Nevertheless, large ungulates exhibited interference competition derived from presence of free-roaming horses. Conclusion: This review identified patterns and gaps in our current knowledge about the effect of horse presence on wild mammals, and can help to readdress further research. Therefore, we recommend careful monitoring of horses and their potential effects on wildlife by using species proxies such as ungulates and rodents to determine if the presence of horses in protected areas affects conservation objectives.